Effect of Breast Milk Expression during Kangaroo Mother Care on Milk Volume in Mothers with Premature Infants Admitted to Neonatal Intensive Care Unit - Mahdiye Mansoori; Naiire Salmani (Mashhad University of Medical Sciences, 2020)
Background: Breastfeeding is a two-way interaction between mother and infant, the sustainability of which requires the presence of both parts given their complementary roles. Aim: The present study was conducted to investigate the effect of breast milk expression during kangaroo mother care (KMC) on milkvolume in mothers with premature neonates.   Method: This quasi-experimental study was performed on 40 mothers with premature newborns admitted to a neonatal intensive care unit in a city in the west of Iran in 2019. The participants were randomly assigned into two groups of intervention and control. Breast milk in both groups was expressed 8 times a day from day 4 to day 6 after birth using a 20-cc syringe and recorded in a checklist. In the intervention group, two milking sessions were performed during the KMC. However, in the control group, milking was conducted according to the ward routine. Data were analyzed in SPSS software (version 23) using repeated-measures ANOVA. Results: The mean ages of the participants in the intervention and control groups were 29.05±4.09 and 27.85±3.58 years, respectively. There was a statistically significant difference between the milkvolume of the intervention and control groups on days 4 (P=0.04), 5 (P=0.02), and 6 (P=0.007) and between the total volume of milkduring the three days (P=0.01). Implications for Practice: Breast milk expression duringKMC could have a positive effect on increasing milkvolume. Therefore, can be recommended as an intervention to support mothers with insufficient milk.